Internet Security Threats and Risks for Alpha Generation in Indonesia - Natasya Misnawati Sikki; Olivia E.S Liando; John Reimon Batmetan (JR Education, 2022)
The Internet can be a wonderful place for learning, shopping, playing games, and connecting with our friends. Unfortunately, there are also predators, identity thieves, and so on online, that might try us. To be safe online, it is important for us and our children to be aware of the dangers. The purpose of this research is to find out how dangerous and how big the influence of the internet is on minors. Here the researcher uses quantitative methods to formulate Internet strategies for minors. The results of this research can be formulated that the use of the internet for minors is very dangerous because there are many negative impacts of the internet that can make children lazy, minors can use the internet with the assistance of parents and make the internet a means of learning for children to grow and develop. With this, it can be said that the role of parents is very important for children when using the internet so that no dangerous things can be accessed by children when using the internet.